If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4f+4=6f-2
We move all terms to the left:
4f+4-(6f-2)=0
We get rid of parentheses
4f-6f+2+4=0
We add all the numbers together, and all the variables
-2f+6=0
We move all terms containing f to the left, all other terms to the right
-2f=-6
f=-6/-2
f=+3
| -4(4x+5)-5=-4(x+1)+2x | | -7(2-4x)=16 | | 15+10x=14x | | 9(q-4)=81 | | 3(3x-4)=6x-9 | | -8(2+x)=-24 | | X-5=2√(x+3) | | 8(x-4)=-4(x-16)= | | 8=v/8+1 | | 3x=2x=50=180 | | 3+8x=3x(3) | | -4x-5-8x+10=8 | | X=9-8x21-2x | | 24-18x+6=12x-8-14x | | 75x-4=45x+5 | | -4/5t(2/5)=2/3 | | -12(x+8)=4(x+8)= | | 13y+2=20y+5 | | 5z-71=74 | | -7n+1=17 | | 8(x+9)=7x+7 | | 9/4*y−12=1/4*y−4 | | 2x-4=55.2 | | 5/8(x)=2/4 | | 6-7x=7x-10x-19 | | X+0.4=0.8k | | 3/5(s-5)=-6 | | 3/8x+1/6+5/12=69 | | 5x-6+76=180 | | 3(4x-2)-14=8+4(2x-2) | | 5x-6=76 | | 5/8x=2/4 |